EFL Teachers’ Awareness and Tolerance of Thai Undergraduates’ Syntactic Writing Errors - Bosuwon, Takwa (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2014)
This survey study investigated non-native EFL teachers’ awareness and tolerance of Thai undergraduates’ syntactic writing errors. The instrument for collecting data was a twenty-page questionnaire based on the nineteen types of Thai students’ written errors personally experienced by the researcher and revealed by other research. Excluding miscellaneous errors, the results show that 16 errors were moderately found (41-60%) and 2 errors were close to most frequently found (61-80%). They were article and verb tense. The top-five most frequently found errors included article, verb tense, run-on sentence, fragment, and subject-verb agreement, respectively. Five errors with percentages of L1 interference close to 50% or higher were word order, fragment, run-on sentence, over-marking of conjunction, and singular or plural form. Among all given intralingual causes, incomplete application of rules and ignorance of rule restrictions received higher percentages than others. Regarding teachers’ tolerance of the 18 errors, all except one error (preposition) were to be corrected immediately or as soon as possible. There was no correlation between error frequency and error tolerance except from article (insertion) and subject-object pronoun. There was also no correlation between error type (global or local) and error tolerance except from verb tense (sequence) and modal verb.